What women want: Women's health in Rural and Regional Australia – Insights from an interprofessional research collaboration between academic researchers, nursing clinicians, and industry professionals. (28th November 2021) - Sivertsen, Nina; Abigail, Wendy; Tieu, Matthew; Eastman, Maree; McCloud, Christine; Thomson, Wendy; Tonkin, Helen
Abstract: The aim of this study was to (a) investigate community women's knowledge and experiences of women's health community services in northern rural and regional New South Wales, Australia; (b) identify any existing gaps in community women's health programs in this region and (c) to contribute to service provision, strategic planning, and industry professional development of community nurse researchers in collaboration with industry. The research took place in Northern New South Wales Local Health District (NNSWLHD) Australia, which is comprised of Tweed/Byron, Richmond and Clarence Health Service Groups, during May to September 2019. Participants comprised 13 women's health service clients over the age of 18 years and less than 74 years, attending health services clinics within NNSWLHD. The research was undertaken as a partnership between three senior healthcare professionals (Clinical Nurse Consultants), one from each Health Service Group, and academic researchers, who provided the key senior healthcare professionals with research training and guidance. Key themes related to primary healthcare experiences and needs of women living in NNSWLHD, and the quality of women's primary healthcare services in that region. Thematic analysis revealed four key themes and several sub‐themes. These were (1) Knowledge and Awareness of Services, (2) Barriers to Access, (3) Personal Issues and (4) A Need for Women‐Centred Care. The major issues women experienced were deficits in services, lengthy wait times and poor access. Additional funding is necessary to uphold community women's health nurse positions in rural health to improve women's health outcomes in these locations.